Effect of CO–CO2 and H2–H2O on the reduction degree of fluxed pellets: reduction mechanism within hydrogen-rich blast furnace. (21st October 2022) - Xu, Chenyang; Xu, Anjun; Zhang, Jianliang; Liu, Zhengjian; Wang, Yaozu; Wang, Rongrong; Zheng, Anyang; Ma, Liming
ABSTRACT: In order to explore the mechanism of hydrogen-rich blast furnace on improving the reduction behaviour of fluxed pellets, the isothermal reduction experiments of fluxed pellets in CO-CO2 -N2 and CO-CO2 -H2 -H2 O-N2 atmosphere were studied. The results show that the condition of hydrogen-rich blast furnace at 900°C has a significant effect on improving the reduction degree of fluxed pellets. It is helpful to increase the reduction rate of fluxed pellets at 1000~1100°C. The phenomenon of "reduction stagnation" at 800°C is due to the metallic iron layer formed on the periphery of the fluxed pellets, which hinders the entry of reducing gas. The morphological observation of the reduction products showed that the grid-like metallic iron structure is the key factor to improve the reduction rate and reduction degree of fluxed pellets in CO-CO2 -H2 -H2 O-N2 . Finally, the reduction mechanism of flux particles in hydrogen-rich blast furnace is summarized.